Food habit, physical activity and nutritional status of adolescents in selected schools of Madhyapur Thimi municipality, Nepal: A cross-sectional study. - Samiksha Baral; Anil Kumar Singh; Arjun Aryal; Jwala Subedi; Utsav Dhakal; Anita Khanal (PLOS Global Public Health)
A dramatic rise in obesity is caused by unhealthy eating habits combined with lower levels of physical activity, and the under nutrition problem is still unresolved. Focusing on the nutritional needs of adolescents could be a significant step toward breaking the vicious cycle of malnutrition, chronic diseases, and poverty. This study aims to assess food habit, levels of physical activity and nutritional status of adolescents in Madhyapur Thimi Municipality, Bhaktapur. A cross-sectional descriptive study design was conducted. Cluster random sampling technique with validated, self-administered questionnaire was used for data collection. Ethical approval, written informed consent and assent were obtained. International Physical Activity Questionnaire (IPAQ) was used to measure level of physical activity. Nutritional Status was measured in terms of BMI for age z-score. Height and weight were measured by using UNICEF Stadiometer and Seca Scale. Data were analyzed using Chi-square test and logistic regression analysis was applied for the further analysis using SPSS V 20. Among the 460 participants, 19.6% were overweight, while 8.5% were underweight. Factors showing a statistical association with being overweight included the mother's occupation, fruit avoidance, exposure to mass media advertisements, junk food consumption. Almost all the participants (93%) consumed junk food with (57.5%) consuming daily or alternately. Regarding physical activity, 65.4% of participants engaged in moderate activity, 30.7% were inactive and only 3.9% engaged in high levels of physical activity. The level of physical activity did not show a significant association with being overweight. Public health nutritionists should actively engage adolescents in developing interventions that promote healthy eating habits and reduce junk food consumption, as adolescents are more susceptible to food marketing than adults. Physical activity alone may not be responsible for being overweight as dietary modification plays vital role in maintaining normal body weight.